Analysis of the predictors of hypertrophic scarring pain and neuropathic pain after burn. Issue 6 (September 2022) - Shu, Futing; Liu, Huazhen; Lou, Xiaozhen; Zhou, Zixuan; Zhao, Zhihao; Liu, Yingying; Bai, Xueli; Luo, Pengfei; Zheng, Yongjun; Xiao, Shichu; Xia, Zhaofan
Highlights: The survival rate of severe burns has been significantly improved. Hypertrophic scarring pain after a burn injury is a common problem. Progression of hypertrophic scarring pain must be prevented. This article is of utmost importance to guide the individualized pain management and improve patients' life quality. Abstract: Introduction: Burn hypertrophic scarring pain is a common and perennial complaint which not only affects patients' quality of life, but also their recovery and reintegration. Physical therapy and medicine regimens are all available for the treatment of hypertrophic scarring pain. Unfortunately, the efficacy of clinical practice is not very satisfactory and the management of hypertrophic scarring pain remains challenging. Therefore, it is of utmost importance to explore the risk factors for hypertrophic scarring pain and further identify whether it is neuropathic pain, aiming to guide the clinical therapy and help patients live a pain-free life. Methods: This retrospective study enrolled patients with postburn hypertrophic scarring pain between 2017 and 2020 in a burn center in Shanghai. Research objects were included strictly according to the inclusion criteria and every enrolled patient was included in the study only once. Demographic information, burn and scar characteristics, and pain scores were collected through the Changhai Hospital Medical Information System, patient questionnaire and physician assessment. Using SPSS 26.0 software, the data were first processed by descriptive statistics, and linear and logistic regression analyses were further employed to explore the significant factors. Results: The sample involving 123 patients was consisted of 56.9% males, 79.7% caused by fire with a median age 40.5 years, total body surface burn-area (TBSA) 44.4%, wound healing time of target scar 57.9 days, hyperplasia time 9.3 months and the scar location mainly in the limbs (55.3%). Of all the included objects, the modified Vancouver Scar Scale (mVSS) total, visual analogue scale (VAS) score, brief pain inventory (BPI) total and the percentage of neuropathic pain were 9.6, 3.3, 36.0 and 74.8%, respectively. Integrating covariates with a P value of <0.10 through preliminary univariate analysis, multivariable linear regression showed sex (P = 0.049), age (P = 0.020), target scar location (P = 0.017, P = 0.254), and pliability (P = 0.016) were linked with severe VAS score; and burn depth of target scar (P = 0.023), hyperplasia time (P = 0.027, P = 0.001), vascularity (P = 0.028), and pliability (P = 0.001) were associated with higher BPI score. Adjusting for potential confounders, hyperplasia time (P = 0.005, P = 0.039) was found to be the only independent risk factor for hypertrophic scarring neuropathic pain in the multivariate logistic regression analysis, with mVSS total of P = 0.062. Conclusions: The model in our study has clarified that sex, age, target scar location, burn depth of target scar, hyperplasia time, and vascularity, especially pliability, may provide excellent prediction of hypertrophic scarring pain outcome; for neuropathic pain, only hyperplasia time has further prospects, with mVSS total as a potential forecast. In an era increasingly aware of life quality, this work may contribute to the elaboration of strategies to hypertrophic scarring pain management, provide an individualized therapy, and help patients live a pain-free life.